2020
DOI: 10.11591/ijere.v9i3.20580
|View full text |Cite
|
Sign up to set email alerts
|

The role of entrepreneurial intention in predicting vocational high school students’ employability

Abstract: One of the factors that contribute to the level of employability is entrepreneurial intention. This study discusses the role of entrepreneurial intentions on students' employability. The population in this study was all students of grade XII of Vocational High School Koperasi Yogyakarta, Indonesia, consisting of 141 students. The sample in this study was 86 students. The sample selection was done by randomizing using a cluster random sampling technique. Methods of data collection used in this study are scales,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The intention to do business is an important matter, and it must be instilled in vocational high school students [27]. The research result shows that the intention to do business contributes to the students' employability in vocational high schools [28].…”
Section: Personalitymentioning
confidence: 90%
“…The intention to do business is an important matter, and it must be instilled in vocational high school students [27]. The research result shows that the intention to do business contributes to the students' employability in vocational high schools [28].…”
Section: Personalitymentioning
confidence: 90%
“…The findings of this study are different from previous studies. The results of previous studies that examined workreadiness found that factors related to workreadiness were self-concept and perception of the learning environment [49], entrepreneur intention and responsibility [50,51], academic achievement and self-concept [29], motivation to learn and social support [11]. This research is expected to develop the results of previous research to be more comprehensive in uncovering the problems of student work readiness.…”
Section: Multiple Linear Regression Analysismentioning
confidence: 91%
“…Quantitative research methods are methods based on the philosophy of positivism (Mustafa et al, 2020;Nasution, 2017). Furthermore, what is included in the assumption test is the normality test, linearity test (Tentama & Yusantri, 2020). The test is used as a condition for testing the hypothesis (Fahruddin et al, 2016).…”
Section: Methodsmentioning
confidence: 99%